2020
DOI: 10.1177/0954405420933708
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic modeling and control of mobile robot for large-scale workpiece machining

Abstract: Safety and reliability are significant in the sense of robotic machining for large-scale workpieces. In this article, a control scheme is proposed to ensure the safe motion of the mobile robot. Screw theory is used to analyze the motion of the mobile robot. The mobile platform with Mecanum wheels can be considered as a mechanism with four driven screws in series. An auxiliary reference position of the mobile platform is calculated based on the kinematic model, and the motion of the mobile platform and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In intelligent manufacturing, the MWMR is integrated with an industrial IoT-based system to intra-factory logistics automation [3]. In addition, the MWMR is also integrated with a manipulator to perform different tasks such as: machining large-scale wind turbine blades by the mobile robots [4]; the robot surveillance of the Super Proton Synchrotron accelerator of the European Organization for nuclear research [5]; and the aromatherapy robot delivers therapeutic vaporized essential oils or drugs needed to prevent or treat Covid-19 infections [6]. However, for the MWMRs to work effectively in a system the main problem is to control its movement precisely following the desired trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…In intelligent manufacturing, the MWMR is integrated with an industrial IoT-based system to intra-factory logistics automation [3]. In addition, the MWMR is also integrated with a manipulator to perform different tasks such as: machining large-scale wind turbine blades by the mobile robots [4]; the robot surveillance of the Super Proton Synchrotron accelerator of the European Organization for nuclear research [5]; and the aromatherapy robot delivers therapeutic vaporized essential oils or drugs needed to prevent or treat Covid-19 infections [6]. However, for the MWMRs to work effectively in a system the main problem is to control its movement precisely following the desired trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the research field of industrial robot, there are a number of recently published studies that have reported the data transmission between product design data and robotic platforms for manufacturing such as Tao et al [ 26 ], Jokić et al [ 27 ], Izagirre et al [ 28 ], Zhang et al [ 29 ], and Li et al [ 30 ]. However, the authors found that there is still relatively little information on the data penetration between the building digital designs and robotic platforms.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates the robotic machining of large-scale workpieces with higher positional accuracy. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates the robotic machining of large-scale workpieces with higher positional accuracy. 11,12 SwarmItFIX (Figure 1) is one such patented mobile RFA setup that supports sheet metals at the bottom when machining happens on top of the metal sheet. 13,14 It follows the five-step sequence to traverse between any two support locations.…”
Section: Introductionmentioning
confidence: 99%